Emerging animal viruses: real threats or simple bystanders? - Eduardo Furtado Flores; Rudi Weiblen; Juliana Felipetto Cargnelutti; Fernando Viçosa Bauermann; Fernando Rosado Spilki; Enio Mori; Ana Cláudia Franco (Pesquisa Veterinária Brasileira, 2013)
The list of animal viruses has been frequently added of new members raising permanent concerns to virologists and veterinarians. The pathogenic potential and association with disease have been clearly demonstrated for some, but not for all of these emerging viruses. This review describes recent discoveries of animal viruses and their potential relevance for veterinary practice. Dogs were considered refractory to influenza viruses until 2004, when an influenza A virus subtype H3N8 was transmitted from horses and produced severe respiratory disease in racing greyhounds in Florida/USA. The novel virus, named canine influenza virus (CIV), is considered now a separate virus lineage and has spread among urban canine population in the USA. A new pestivirus (Flaviviridae), tentatively called HoBi-like pestivirus, was identified in 2004 in commercial fetal bovine serum from Brazil. Hobi-like viruses are genetically and antigenically related to bovine viral diarrhea virus (BVDV) and induce similar clinical manifestations. These novel viruses seem to be widespread in Brazilian herds and have also been detected in Southeast Asia and Europe. In 2011, a novel mosquito-borne orthobunyavirus, named Schmallenberg virus (SBV), was associated with fever, drop in milk production, abortion and newborn malformation in cattle and sheep in Germany. Subsequently, the virus disseminated over several European countries and currently represents a real treat for animal health. The origin of SBV is still a matter of debate but it may be a reassortant from previous known bunyaviruses Shamonda and Satuperi. Hepatitis E virus (HEV, family Hepeviridae) is a long known agent of human acute hepatitis and in 1997 was first identified in pigs. Current data indicates that swine HEV is spread worldwide, mainly associated with subclinical infection. Two of the four HEV genotypes are zoonotic and may be transmitted between swine and human by contaminated water and undercooked pork meat. The current distribution and impact of HEV infection in swine production are largely unknown. Avian gyrovirus type 2 (AGV2) is a newly described Gyrovirus, family Circoviridae, which was unexpectedly found in sera of poultry suspected to be infected with chicken anemia virus (CAV). AGV2 is closely related to CAV but displays sufficient genomic differences to be classified as a distinct species. AGV2 seems to be distributed in Brazil and also in other countries but its pathogenic role for chickens is still under investigation. Finally, the long time and intensive search for animal relatives of human hepatitis C virus (HCV) has led to the identification of novel hepaciviruses in dogs (canine hepacivirus [CHV]), horses (non-primate hepaciviruses [NPHV] or Theiler's disease associated virus [TDAV]) and rodents. For these, a clear and definitive association with disease is still lacking and only time and investigation will tell whether they are real disease agents or simple spectators.